HINDU DAN DEMOKRASI - Rudita, I Made (Jurnal Advokasi, 2016)
Hinduism is a religion that up hold the principles of democracy, because it gives freedom Hindu followers the choice way or the way to believe in God, according to his conscience. Besides Hindu religion is very appreciate the difference and diversity, in line with the motto of âBhineka Tunggal Ikaâ that is the essence of Hinduism. Further more Hindu always teach people to be critical and honest, which is in line with the attitude of thinking of democracy